2021
DOI: 10.1186/s40942-020-00254-9
|View full text |Cite
|
Sign up to set email alerts
|

Macular edema after rhegmatogenous retinal detachment repair: risk factors, OCT analysis, and treatment responses

Abstract: Purpose To investigate risk factors, imaging characteristics, and treatment responses of cystoid macular edema (CME) after rhegmatogenous retinal detachment (RRD) repair. Methods Consecutive, retrospective case–control series of patients who underwent pars plana vitrectomy (PPV) and/or scleral buckling (SB) for RRD, with at least six months of follow-up. Clinical and surgical parameters of patients with and without CME (nCME), based on spectral-dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 31 publications
3
32
0
1
Order By: Relevance
“…CME diagnosis was defined as hyporeflective spaces regardless of the retinal layer involved. CRT was not considered for analysis because of the varying degree of macular atrophy [ 23 ]. SD-OCT characteristics were collected, such as the presence of ERM, central retinal thickness (CRT), outer retinal layer alterations (inner and outer segment junction (IS/OS) and/or external limiting membrane disruption), and localization of cysts in the inner retinal layers (IRL) or outer retinal layers (ORL).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CME diagnosis was defined as hyporeflective spaces regardless of the retinal layer involved. CRT was not considered for analysis because of the varying degree of macular atrophy [ 23 ]. SD-OCT characteristics were collected, such as the presence of ERM, central retinal thickness (CRT), outer retinal layer alterations (inner and outer segment junction (IS/OS) and/or external limiting membrane disruption), and localization of cysts in the inner retinal layers (IRL) or outer retinal layers (ORL).…”
Section: Methodsmentioning
confidence: 99%
“…The rate of CME after primary RRD repair ranges from 6% to 36%, regardless of the surgical technique used [ 8 , 9 , 20 , 21 , 22 ]. Age, lens status (pseudophakia and aphakia), macular status, and the severity of the retinal detachment, especially with proliferative vitreoretinopathy (PVR), are reported to be risk factors for CME after primary RRD repair [ 9 , 20 , 23 , 24 ]. Recently, Pole et al showed a relationship in univariate analysis between the number of surgeries, macular status, PVR grading, and the occurrence of CME, but these parameters were no longer significant in multivariate analysis [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of CME secondary to RRD repair across included studies was unclear given the variable study design and surgical approach along with limited, nonspecific, and nonstandardized reporting of this complication between studies [45, 72]. Pre- and postoperative precautions such as the use of anti-inflammatory medications [66, 73], surgical techniques such as inner limiting membrane peeling [74, 75], and advancements in optical coherence tomography to monitor for developing CME [72] may aid in preventing, diagnosing, and managing CME following RRD repair. Furthermore, a lack of available data on CSFT at baseline and postoperatively made it difficult to calculate mean differences in retinal thickness over time.…”
Section: Discussionmentioning
confidence: 99%
“…Cystoid macular edema (CME) is well-reported following retinal detachment repair with SB and PPV with the incidence of CME post-PPV reported in 2.3-16.3% of cases [66][67][68] versus 6.9-43% with SB [68][69][70][71]. The risk of CME secondary to RRD repair across included studies was unclear given the variable study design and surgical approach along with limited, nonspecific, and nonstandardized reporting of this complication between studies [45,72]. Pre-and postoperative precautions such as the use of anti-inflammatory medications [66,73], surgical techniques such as inner limiting membrane peeling [74,75], and advancements in optical coherence tomography to monitor for developing CME [72] may aid in preventing, diagnosing, and managing CME following RRD repair.…”
Section: Table 3 (Continued)mentioning
confidence: 99%